INTEGRASI NILAI-NILAI KEARIFAN LOKAL MINANGKABAU KE DALAM MATERI AJAR SOSIOLOGI DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Erianjoni, Erianjoni (TINGKAP, 2015)
This article presents a discussion on the learning strategy of how to integrate the sociological concepts and principals in order to shape student’s character by way of using the Minangkabau local wisdom. Such strategy could be done, among others, by integrating sociological concepts and scientific sociological principles with cultural values of Minangkabau, as it is reflected in local proverbs, traditional poetries (pantun), aphorism etc. Finding out the relation sociological concepts with the local cultural values is merely one step. Further step is to single out the idea behind local cultural values as a tenet in which the students could learn much about good characters they should pursue. Endeavour to integrate local characters values with the subject of sociology should refer to existing curriculum in sociology accordingly in which the syllabus, core competency, basic competency and its indicators are included as learning instruments (RPP) and learning processes in the class as well. Keywords: Integration, culture value, character